Effects of online consumer reviews on firm-based and expert-based communications. Issue 1 (12th March 2018) - Zhu, Jianjun; Tse, David K.C.; Fei, Qiang
Abstract : Purpose: To explain and empirically test how different marketing communication channels interact with each other and contribute to brands' diverging marketplace performance. Design/methodology/approach: With a unique data set combining key variables of major passenger car brands, the paper takes a source-based perspective to investigate how firm-based communications, expert opinions and online consumer reviews interact and affect brands' marketplace performance. Then the paper studies the three special boundary conditions under which online consumer reviews' influence varies in competition with the other two established information sources. Lastly, a study was done to demonstrate the financial significance of investing in different information sources. Findings: The results show that online consumer reviews mitigate the effectiveness of the other two information sources in driving brand sales. This mitigation effect is also magnified when the brand is weak, firm-based communications are modest and expert opinions are less favorable. The findings further suggest that in the emerging communication enterprise, firm-based and expert-based communications remain the core while user-based communication plays an indispensable competing and complementary role. Practical implications: In the new digital era, firms are facing the daunting task of understanding and integrating multiple communication channels. The study provides important implications for both researchers and practitioners with respect to brand management and integrated communications. Originality/value: Existing studies have demonstrated that each of the three communication efforts (by firms, experts and consumers) exerts a significant influence on product sales, but few studies have been conducted in settings marked by the coexistence of these efforts. In addition, the three communication efforts are likely to have different effects on brands with different market positions. The current study is contributing to the literature by filling the above gaps.